In-between spaces and social interaction: a morphological analysis of Izmir using space syntax - Can, Işın; Heath, Tim (Springer Verlag, 2015)
This research tackles the intermediate spaces between buildings and the street, by examining the definition and importance of spatial configuration in relation to urban morphology and social relations. It also analyses how the organisation of in-between space affects social interaction in different urban forms. To understand the complex relations and socio-spatial structure of the city, it is important to use mixed methods. This research utilises various methods to focus on three dissimilar urban morphologies in Izmir, Turkey. Two inner city quarters and one modern housing estate of middle- and high-income groups are compared using space syntax analysis and snapshot observations. These neighbourhoods are selected according to their syntax measures from more integrated to segregated neighbourhoods in the axial analysis. And for a detailed zoomed-in analysis, similar diameter areas are covered for observations. Subsequently, activity patterns are observed at different times of the day, one weekday and one Sunday in three cases. In each neighbourhood, syntactic measures of all selected streets are correlated with these recorded activities. This study reveals that connectivity of streets is important for supplying niches that trigger long-duration activities and social interaction. In modern estates, stationary activities are not correlated strong enough with movement as it is in inner city neighbourhoods. Additionally, in-between spaces increase the frequency of social interaction and co-presence of people particularly in more integrated areas. However, this is only one element in developing sense of community. Further research is needed especially in correlating space syntax with environmental issues, as well as people’s behaviour.